2014
DOI: 10.1099/vir.0.060046-0
|View full text |Cite
|
Sign up to set email alerts
|

Variable region of the 3′ UTR is a critical virulence factor in the Far-Eastern subtype of tick-borne encephalitis virus in a mouse model

Abstract: Tick-borne encephalitis virus (TBEV) is a major arbovirus that causes thousands of cases of severe neurological illness in humans annually. However, virulence factors and pathological mechanisms of TBEV remain largely unknown. To identify the virulence factors, we constructed chimeric viruses between two TBEV strains of the Far-Eastern subtype, Sofjin-HO (highly pathogenic) and Oshima 5-10 (low pathogenic). The replacement of the coding region for the structural and non-structural proteins from Sofjin into Osh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 47 publications
1
42
0
Order By: Relevance
“…It is likely that replacement in the chimera of two LGTV genes for the corresponding genes of TBEV created LGTV-TBEV protein incompatibilities that compromised chimeric virus replication in vivo, altered virus-host interactions, and resulted in the reduction of neuroinvasiveness. Our data are in a good agreement with those observed by Sakai et al, 2014 for chimeric TBEV viruses constructed between TBEV Sofjin (highly pathogenic) and Oshima (low pathogenic) strains of TBEV (Sakai et al, 2014). Replacement of structural protein genes of Oshima genome with corresponding genes derived from Sofjin genome reduced chimeric virus replication in mouse neuroblastoma cells and exhibited neuroinvasiveness similar to that of the parental low-pathogenic Oshima strain”.…”
Section: Results and Disscussionsupporting
confidence: 90%
“…It is likely that replacement in the chimera of two LGTV genes for the corresponding genes of TBEV created LGTV-TBEV protein incompatibilities that compromised chimeric virus replication in vivo, altered virus-host interactions, and resulted in the reduction of neuroinvasiveness. Our data are in a good agreement with those observed by Sakai et al, 2014 for chimeric TBEV viruses constructed between TBEV Sofjin (highly pathogenic) and Oshima (low pathogenic) strains of TBEV (Sakai et al, 2014). Replacement of structural protein genes of Oshima genome with corresponding genes derived from Sofjin genome reduced chimeric virus replication in mouse neuroblastoma cells and exhibited neuroinvasiveness similar to that of the parental low-pathogenic Oshima strain”.…”
Section: Results and Disscussionsupporting
confidence: 90%
“…The longer VRs of natural isolates suggest increased length may have a selective advantage during infections in vector or host species. However, a shorter VR in a tick borne encephalitis genome was associated with higher virulence in a mouse model (Sakai, Yoshii et al 2014). The VR of mosquito-borne flaviviruses contains an A-U rich region that is thought to have evolved due to the RdRp stuttering on the UAA stop codon.…”
Section: Additional Conserved 3′ Ncr Sequencesmentioning
confidence: 99%
“…Virus titers were determined by plaque assay using baby hamster 98 kidney (BHK-21) cells as described previously (Sakai et al, 2014). Plaque assays in NA 99 cells showed that the mutant viruses had growth similar to that of Oshima-IC-pt, but 100 significantly lower than that of Sofjin-IC-pt (Fig.…”
mentioning
confidence: 99%